2011
DOI: 10.1007/s12639-011-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of cystic echinococcosis in slaughtered herbivores in Sari abattoir, North of Iran

Abstract: A study was conducted to assess the ruminants' hydatidosis in Mazandaran Province, Northern Iran. A total, 1,799 sheep, 985 goats and 362 cattle slaughtered at Sari industrial slaughter house were examined for hydatid cyst infection. The results indicated that 65.2% of sheep, 37.8% of goats and 40.1% of cattle were infected. The liver and lung infection rate in sheep were 18.8 and 4.3%, goats 17.2 and 12.6% and cattle 44.1 and 7.6%, respectively. The study showed that 766 (45.3%) out of 1,691 infected animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
2
8
1
Order By: Relevance
“…In appropriate human practices and behavior and closely communication to dogs may remain as a main danger to public health [31] , [32] . On the other hand, a recent study in slaughtered herbivores in Mazandaran demonstrated the situation of CE infection in livestock as followed 65.2%, 37.8% and 40.1% in sheep, goats and cattle; respectively [33] . These data confirms the high infection rate of CE among domestic animals in the area.…”
Section: Discussionmentioning
confidence: 93%
“…In appropriate human practices and behavior and closely communication to dogs may remain as a main danger to public health [31] , [32] . On the other hand, a recent study in slaughtered herbivores in Mazandaran demonstrated the situation of CE infection in livestock as followed 65.2%, 37.8% and 40.1% in sheep, goats and cattle; respectively [33] . These data confirms the high infection rate of CE among domestic animals in the area.…”
Section: Discussionmentioning
confidence: 93%
“…Although the number of sheep and goats is higher than cattle in the studied areas, the CE prevalence rates in Fars are highest in cattle (11%), sheep (just under 5%) and goats (4.5%) [ 31 ]. Also, another study in northern Iran (Mazandaran province), showed that 40.1% of cattle and 37.8% of goats were infected by CE [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several surveys in Iran have indicated CE prevalence in livestock ranging from 1.3 to 74.4% in sheep, 0.4e37.8% in goats, 1.3e40.1% in cattle, 4.3e31.9% in buffalo, 8.8e35.5% in camels and 2% in donkeys (Ahmadi, 2005;Ahmadi and Meshkehkar, 2011;Eslami et al, 2014;Samavatian et al, 2009). In the northern Caspian coastal provinces, prevalence of CE ranged between 14.6 and 65.2% in sheep, 10.1e37.8% in goats and 12e41% in cattle (Mansoorlakooraj et al, 2011;Ziaei et al, 2011). In northwestern areas of the country, prevalence of CE ranged between 22.2 and 74.4% in sheep, 20e25% in goats and 28.3e38.3% in cattle Mirzaei et al, 2015).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%